Analisis Pengukuran Kinerja Keuangan Bank Umum Syariah di Indonesia Menggunakan Metode Risk Based Bank Rating (RBBR) Dan Shariah Conformity And Profitability (SCNP) - Jambak, Arya Neta Adinda; Harahap, Nurlaila; Kusmilawaty, Kusmilawaty (Universitas Labuhanbatu, 2024)
The study aims to find out the level of performance of sharia general Banks in Indonesia by using the risk based rating bank (RBRR) and shariah conexplaining and profitability (SCNP) period 2018-2020. He said the rupiah was expected to strengthen to rp9,100 per dollar in the Jakarta interbank spot market on Tuesday. The technique used for this research is overwhelmingly sampling by using descriptive quantitative methods. The study described the performance of the sharia general bank by two methods of risk-based rating bank (RBBR) as a result of the four aspects of the risk profile, good corporate governance, integrity integrity, and capital. The second method is the shariah contact and profitability (SCNP), viewed by the sharia-based variables with islamic income ratio, islamic income ratio, and profit sharing share as well as return on assets (roa), return on equity (roe), and net profit margin ratio. Research indicates that using risk-based rating bank (RBBR), the sharia general bank is in